ANALYSIS OF SUSTAINABILITY PERFORMANCE, GREEN ACCOUNTING AND ESG DISCLOSURE ON FIRM VALUATION - Ang Swat Lin Lindawati; Tan Geviena Geraldine; Bambang Leo Handoko; Rindang Widuri; Mazlina Mustapha (International Journal of Contemporary Accounting, 2023)
Numbers of public companies whose shares are listed on Indonesia Stock Exchange is growing rapidly. The increase in public companies is phenomenon that describe the confidence of investors to invest in shares of public companies. Firm valuation is an important determining factor for stock investors to choose investment products. Currently firm value is not only seen from the company's ability to generate profits but also seen from other factors related to sustainability. This study aims to obtain empirical evidence on the influence of sustainability performance, green accounting and ESG disclosure on firm value. This study uses a quantitative approach and panel data regression on banking sector companies listed on the Indonesia Stock Exchange for the 2012-2021 period. The analysis technique uses ordinary least squares with statistical software. The results show that sustainability performance has a positive effect on firm value, while green accounting has a negative effect on firm value. On the other hand, ESG disclosure gives no impact on firm value. Sustainability performance and implementation of green accounting needs to be highlighted in order to have a positive impact on the company by increasing the effectiveness and efficiency of its implementation as well as integrating it into its operations.